Effect of the use of internet marketing and e-WOM on brand awareness - Foster, Bob; Deni Johansyah, Muhammad (Opción, 2020)
This study aims to determine the effect of using internet marketing and WOM electronics on buying interest with brand awareness as an intervening variable at Starbucks Coffee Company. This research was conducted using quantitative methods, using path analysis, and using SPSS version 24 software. As a result, internet marketing and e-WOM had a significant influence on brand awareness. In conclusion, it is expected that Starbucks Coffee Company can increase internet marketing and e-WOM so that people become aware of the presence of Starbucks Coffee Company as one of the cafes/hangouts that can be used as a hangout